Biofuels and cross-sectoral agrobusiness in Córdoba, Argentina - Saccucci, Erika (2023)
In this article we carry out a documentary analysis of journalistic notes and secondary sources of the transformation of agrobusiness in the province of Córdoba in Argentina in the context of the global energy crisis and the development of agrofuels. In this scenario, we identified a set of productive sectors that are articulated in a cross-sectoral way, as well as local policies that promote and contribute to consolidate the territory of Cordoba as a strategic enclave at a national level for the production of bioethanol based on corn; which, for example, is expressed in the development of highways to ensure  connectivity between raw material production centres and agro-energy production industries.